BONY LESION ANALYSIS IN CARCINOMA PROSTATE: M.D.P. BONE SCAN VS. GALLIUM-68 PSMA-11 PET/CT - Haider Ali,; Syed Rashid Ul Amin,; Abdul Hai,; Noureen Nizar, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Prostate cancer is the cause of the highest cancer-related death in males, 5-year survival is 31% in metastatic disease, and bone is a common site of metastases. Bone scintigraphy is a routinely used imaging modality for detecting skeletal metastases. It has variable sensitivity of 52-100%, whereas PSMA PET/CT scans have better sensitivity approaching 100%, so we determined the diagnostic accuracy, sensitivity, and specificity of planar M.D.P. (methylene diphosphonate) bone scintigraphy. Methods: This analytical cross-sectional study was conducted at the N.M. & molecular imaging department of S.I.U.T. Karachi. Bone scans and PSMA-PET/CT scans of all patients who were visited from Janury-2018 to January 2023 were reviewed and interpreted by a nuclear physician& radiologist team. Inclusion criteria were histopathology-proven prostate cancer patients who had a bone scan and PSMA PET/CT scan within one month and had not received any treatment between scans. Results: Among 70 scans, 38 (54.2%) were positive for bone lesions. A total of 18 (47%) patients had positive bony lesions on both PSMA-PET/CT and Bone scintigraphy. Among 38 bone lesions positive patients, in eleven patients, bone lesions were detected only on PET/CT scans, whereas nine were positive only on Bone scans. The mean S.U.V. max of all bony lesions was 19.15 (range 3.2-57.5). The bone scan's sensitivity, specificity, and accuracy were 62.07%, 78.05%, and 62.87%, respectively. Conclusion: PSMA-PET/CT is better than bone Scintigraphy for detecting skeletal metastases. However, outcomes of bone scintigraphy may be improved when Tc-PSMA receptor bone scintigraphy is used.